Primiparas’ knowledge on infant health and its relationship with demographic features in Konya (Turkey) - Bodur, Said; Kurşun, Şerife; Çevik, Ümran; Taş, Fatma (Journal of Human Sciences, 2010)
This study was performed to determine the primiparas knowledge level on subjects related infant health and its relationship with their demographic features. This descriptive and cross-sectional study was included 322 primiparas who were delivered in ; Maternity and Child Hospital in ; city-center, in turkey. Data were collected by using a questionnaire which concerns the demographic features, antenatal care and thirty subjects related infant health for measurement of mothers; knowledge level. Of the primiparas, 22% was nineteen years old and lower and educational level of 72% of them was primary school. Mothers; knowledge scores were 44.6+/-12.4 in hundred points in all subjects. There was significant relationship between primiparous mothers educational level, her husbands educational level, number of the antenatal monitoring and total knowledge point related infant health and knowledge scores on infant feeding and infectious diseases. Nominee mothers general educational level must be raised and the frequency of the antenatal monitoring must be increased because primiparas knowledge level on infant health is inadequate in Turkish population.